Step-by-step explanation:
for a³b²c-1d
given
a=2
b=4
c=10
d=15
a³b²c-¹d
=(2³4²10^-1*15
=2³4²15/10
=8*16*15/10
=8*8*3
=64*3
=192
now
a³b²c¹d
=(2³4²10 15)
=(8*16*10*15)
=120*16*10
=1200*16
=19200
Upon first glance of an equation one must look first for parenthesis and solve the contents therein. Next one would need to identify and simplify exponents. Once these steps are well done one needs to look at the whole equation from left to right and solve for any multiplication or division problems and solve them in the order in which they appear. Next one must again look at the equation left to right and solve for any addition or subtraction in the order that they appear within the equation.
1. Reflected over the x- axis
2. Rotated 270 degrees counterclockwise
3. Reflected over the y- axis
The square root of 36 is 6.00. I know this because six squared (6*6) is 36.